Analisis Kesulitan Belajar Siswa Mata Pembelajaran Matematika pada Materi Operasi Hitung Pembagian Kelas III di SD 02 Supriyadi Semarang - Warsono, Didik; Mushafanah, Qoriati; Sukamto, Sukamto (Pena Edukasia, 2023)
The background that prompted this research was that students still found difficulties in solving division problems in class III mathematics material arithmetic operations. The problem in this study is what are the difficulties experienced by class III students of SD Supriyadi 02 Semarang in completing arithmetic operations and what factors cause students to experience learning difficulties in arithmetic operations in class III SD Supriyadi 02 Semarang in completing arithmetic operations of division and to find out what factors cause students to experience difficulties in dividing arithmetic operations in class III SD Supriyadi 02 Semarang. This type of research is descriptive qualitative. Using, test methods, observations, interviews, questionnaires and documentation. The subjects of this study were third grade students at SD Supriyadi 02 Semarang. The results of this study were 28 students in class III SD Supriyadi 02 Semarang, who experienced some difficulties. In this study there were several findings, namely: (1) learning difficulties experienced by third grade students at SD Supriyadi 02 Semarang included a) difficulties restating concepts b) difficulties implementing strategies c) difficulties understanding strategies d) difficulties understanding problems e) difficulties understanding problems f ) difficulty re-examining results and processes. (2) factors that cause difficulty learning division arithmetic operations in class III students of SD Supriyadi 02 Semarang include a) physical factors b) motivational and attitudinal factors c) environmental factors and d) teacher variation factors in teaching.